Modulation of miR‐34a in curcumin‐induced antiproliferation of prostate cancer cells. Issue 9 (1st May 2019) - Zhu, Mingming; Zheng, Zongmei; Huang, Jiaming; Ma, Xiao; Huang, Cong; Wu, Rui; Li, Xiaoting; Liang, Zhaofeng; Deng, Feifei; Wu, Jieshu; Geng, Shanshan; Xie, Chunfeng; et al.
Abstract: Curcumin is a phytochemical which exhibits significant inhibitory effect in multiple cancers including prostate cancer. MicroRNA‐34a (miR‐34a) was found to be a master tumor suppressor miRNA and regulated the growth of cancer cells. To date, however, the role of miR‐34a in the anticancer action of curcumin against prostate cancer has been rarely reported. In the present study, we showed that curcumin altered the expression of cell cycle‐related genes (cyclin D1, PCNA, and p21) and inhibited the proliferation of prostate cancer cells. Furthermore, we found that curcumin significantly upregulated the expression of miR‐34a, along with the downregulated expression of β‐catenin and c‐myc in three prostate cancer cell lines. Inhibition of miR‐34a activated β‐catenin/c‐myc axis, altered cell cycle‐related genes expression and significantly suppressed the antiproliferation effect of curcumin in prostate cancer cells. Findings from this study revealed that miR‐34a plays an important role in the antiproliferation effect of curcumin in prostate cancer. Abstract : In the present study, we showed that curcumin upregulated the expression of miR‐34a and inhibited the proliferation of prostate cancer cells. Inhibition of microRNA‐34a (miR‐34a) activated β‐catenin/c‐myc axis and suppressed the antiproliferation effect of curcumin. Findings from this study revealed that miR‐34a plays an important role in the antiproliferation effect of curcumin in prostate cancer.